Clinical Grade Production of Wilms’ Tumor-1 Loaded Cord Blood-Derived Dendritic Cells to Prevent Relapse in Pediatric AML After Cord Blood Transplantation - Plantinga, Maud; Lo Presti, Vania; de Haar, Colin G.; Dünnebach, Ester; Madrigal, Alejandro; Lindemans, Caroline A.; Boelens, Jaap Jan; Nierkens, Stefan (Frontiers in Immunology, 2020)
Hematopoietic cell transplantation (HCT) is a last resort, potentially curative treatment option for pediatric patients with refractory acute myeloid leukemia (AML). Cord blood transplantation (CBT) results in less relapses and less graft-versus-host disease when compared to other sources. Nevertheless, still more than half of the children die from relapses. We therefore designed a strategy to prevent relapses by inducing anti-AML immunity after CBT, using a CB-derived dendritic cell (CBDC) vaccine generated from CD34+ CB cells from the same graft. We here describe the development and optimization of Good manufacturer practice (GMP)-grade production of the CBDC vaccine. We show the feasibility of expanding low amounts of CD34+ cells in a closed bag system to sufficient DCs per patient for at least three rounds of vaccinations. The CBDCs showed upregulated co-stimulatory molecules after maturation and showed enhanced CCR7-dependent migration towards CCL19 in a trans-well migrations assay. CBDCs expressed WT1 protein after electroporation with WT1-mRNA, but were not as potent as CBDCs loaded with synthetic long peptides (peptide pool). The WT1-peptide pool loaded CBDCs were able to stimulate T-cells both in a mixed lymphocyte reaction as well as in an antigen-specific (autologous) setting. The autologous stimulated T-cells lysed not only the WT1+ cell line, but most importantly, also primary pediatric AML cells. Altogether, we provide a GMP-protocol of a highly mature CBDC vaccine, loaded with WT1 peptide pool and able to stimulate autologous T-cells in an antigen-specific manner. Finally, these T-cells lysed primary pediatric AML demonstrating the competence of the CBDC vaccine strategy.